ANALYSIS OF THE RELATIONSHIP BETWEEN THE INTENSITY OF INTERNET USE AND THE RISK OF DEPRESSION DISORDERS IN STUDENTS OF SENIOR HIGH SCHOOL X IN MATARAM CITY - Srigede, Baiq Kayla (Journal of Innovation Research and Knowledge, 2025)
Background: The pandemic has resulted in significant changes, including internet usage. The total time people spend online during the pandemic has increased significantly. Persistent internet use can have various impacts, leading to the risk of depressive disorders. This study aims to analyze the relationship between internet use intensity and the risk of depressive disorders in adolescents post-pandemic. Research Methods: This study used an observational analytic approach with a cross-sectional design. The instrument used was a questionnaire to measure the level of internet use intensity (KDAI) and the risk of depressive disorders in children (CDI). Participants in this study consisted of students aged 14 to 17 years attending Senior High School X in Mataram City. Respondents met the inclusion criteria and agreed to participate in the study. Students who did not fall into this age group, were in 12th grade, had a history or family history of a mental health disorder diagnosed by a child or psychiatrist, and did not complete the research questionnaire were excluded from the study sample. Results: A total of 115 respondents participated in this study, the majority of whom were 16 years old (47.8%). The incidence of internet use intensity among students post-pandemic was 27.8%. The risk of depressive disorders in students post-pandemic, as detected using the Child Depression Inventory (CDI), was 57.4%. There was a significant association between internet use intensity and the risk of depressive disorders in students post-pandemic (p=0.001). Conclusion: Internet use intensity was significantly associated with the likelihood of depression in students post-pandemic, with the risk increasing by up to 4.1-fold.